P261 Burden of bowel urgency across specific treatment groups among Ulcerative Colitis patients – real world global study analyses. (21st January 2022) - Atreya, R; Redondo, I; Hill, J; Streit, P; Hartz, S; Knight, H; Barlow, S; Hennessy, F; Hunter, T
Abstract: Background: Bowel urgency, the sudden and immediate need to have a bowel movement, is a common symptom in ulcerative colitis (UC) and is associated with higher disease activity, decreased work productivity and markedly reduced quality of life 1 . This study explored differences in disease burden among UC patients with bowel urgency based on their treatment pathway. Methods: Data were extracted from the Adelphi Disease Specific Programme for UC, a point-in-time survey of gastroenterologists (GIs) and patients from Jan 2020-Mar 2021 in Germany, France, Spain, Italy, UK and US. GIs provided patient demographics, clinical characteristics and treatment history. The same patients were invited to complete the Short Inflammatory Bowel Disease Questionnaire (SIBDQ), EQ-5D and Work Productivity and Activity Impairment (WPAI) questionnaire. Three patient subgroups were identified: never received targeted therapy (biologics and JAK inhibitors) (TT-naïve), receiving first TT currently (1L TT) and receiving TT with prior TT use (TT-exp). Within these groups, patients currently experiencing day- or nighttime bowel urgency, reported by physicians, with current treatment duration >3 months, were included. ANOVA, chi-squared and Kruskal-Wallis tests were used to compare the groups. Results: Of the UC patients in the TT-naïve (n=595), 1L TT (n=851) and TT-exp (n=321) groups, 23%, 17% and 26% experienced bowel urgency, respectively. Of those with bowel urgency, TT-naïve patients were younger with lower BMI and the lowest proportion of never smokers vs. the 1L TT and TT-exp groups (Table 1). 70–80% of patients across the three groups remained in non-remission based on the derived Mayo score, while 19% of the TT-naïve group were flaring vs. 18% 1L TT and 32% TT-exp patients (p=0.0324). Steroid use was highest in the TT-naïve group (43%) vs. 10% 1L TT and 17% TT-exp (p<0.0001). 1L TT had the highest number of visits to healthcare professionals in the last 12 months. The patient reported outcome measures indicated substantial and similar quality of life impairment across all patients with bowel urgency (Table 2). The only significant difference was across impairment while working (31% TT-naïve, 17% 1L TT, 28% TT-exp; p=0.0232). Conclusion: This study confirmed that a substantial proportion of patients across all three groups still experience bowel urgency despite receiving treatment. Since bowel urgency is known to negatively impact patients' quality of life, there is a therapeutic need to address this symptom. Reference: 1 . Ha, C, et al. Rectal Urgency Among Ulcerative Colitis and Crohn's Disease Patients: Analyses from a Global Survey. Poster presented at: Digestive Disease Week; 2021 May 21–23; Online event.